Pengaruh Ukuran Perusahaan, Ukuran KAP, Profitabilitas, dan Leverage Terhadap Earning Response Coefficient (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2013) - Keswari, Adjeng Nurdiyah, Dr. Triyono, SE, M.Si (2015)
This research aim to to analyse influence of company size measure, size measure of KAP, profitability, and leverage to coefficients response earnings. Every year-end of company have to report result of its performance in financial statement. Result of which is decanted in financial statement used by the parties which is have importance, one of them investor for the decision making of. Investor of good merespon of financial statement a company if information in it with quality and assumed to draw investor, especially return to be accepted by period to come. This research use method of purposive sampling in election of sampel. Pursuant to used to be criterion to be obtained by sampel counted 186 company, but 42 among others represent data of outlier. Data obtained from publication report annual and of histori company share price. Analysis method weared in this research is analysis of regresi doubled linear. Result of research indicate that measure of company, measure of KAP and profitability have an effect on signifikan to coefficients response earnings, while leverage do not have an effect on signifikan to coefficients response earninngs. Keyword: measure of company, measure of KAP, profitability, leverage, coefficients response earnings.